2019
DOI: 10.1021/acs.energyfuels.9b02720
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Gaseous Hydrogen Sulfide by a Photo-Fenton Wet Oxidation Scrubbing System

Abstract: In this article, a photo-Fenton wet oxidation scrubbing system was used to remove and oxidize gaseous hydrogen sulfide in an ultraviolet (UV)-bubbling column scrubber. The technical feasibility of the removal process of gaseous hydrogen sulfide using a wet oxidation scrubbing system was verified, and the effect of technological parameters (hydrogen peroxide concentration, UV-light power, ferrous ion concentration, pH value of solution, mixed gas flow rate, reaction temperature, and hydrogen sulfide concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…Thus, the high gas-liquid ratio improves the H2S conversion percentage. This increasing trend in our work was found to be similar [20] As a result, it was evident that an increase in liquid-gas ratio shows a significant increase in H2S conversion. However, since more liquid-gas ratio needs more investment, the most appropriate liquid-gas ratio should be determined by considering efficiency and energy costs.…”
Section: Effects Of Liquid-gas Ratio On H2s Conversionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, the high gas-liquid ratio improves the H2S conversion percentage. This increasing trend in our work was found to be similar [20] As a result, it was evident that an increase in liquid-gas ratio shows a significant increase in H2S conversion. However, since more liquid-gas ratio needs more investment, the most appropriate liquid-gas ratio should be determined by considering efficiency and energy costs.…”
Section: Effects Of Liquid-gas Ratio On H2s Conversionsupporting
confidence: 83%
“…The removal of H2S gas was investigated [4], who examined the conversion of H2S from generating coal mining area. Another interesting study was published [20], who studied the conversion of H2S in the presence of UV radiation as a catalyst in order to remove of H2S. However, the studies related to remove H2S from the gas phase using the Fenton process are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The typical dry method mainly includes adsorption separation using various adsorbents (such as activated carbon, molecular sieve, graphene material, metal organic framework), plasma degradation, photocatalytic oxidation, photochemical removal, ozonization 7–12, etc. The typical wet method is represented by solution absorption (such as ethanolamine solution, sodium carbonate solution, ionic liquids, complexing agents 13–15), biological technology (such as biofilter, biological trickling filter, membrane biological scrubber 16–18), catalytic oxidation, new free radicals advanced oxidation absorption techniques, etc. 19–23.…”
Section: Introductionmentioning
confidence: 99%
“…19–23. Moreover, some new wet methods such as Fenton‐like reagents, and photo‐Fenton wet oxidation have been developed 9, 13. These methods have good prospects in some aspects but most of them still have disadvantages such as low removal efficiency, relatively high cost, corrosiveness, and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant results ,, have shown that ultraviolet (UV)-light can effectively decompose PS and PMS to generate SO 4 • – radicals (see Table ). Photochemical SO 4 • – -based AOTs have received extensive attention in pollution control field owing to simple and green process, high reagent utilization, and free radical yield. ,, Liu et al proposed a NO removal process using UV (254 nm)/PS AOT in an UV-impinging stream reactor with vertical lamp tubes, and studied the performance, mechanism and mass transfer-reaction kinetics of NO removal using this technology. Their results indicated that the removal efficiency of NO reached 90.6%, and SO 4 • – and •OH were confirmed as the major active species for NO removal.…”
Section: Progress In So4•–-based Aots For Gaseous Pollutant Removalmentioning
confidence: 99%